2022
DOI: 10.3390/ijms23073556
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Microscopic and Macroscopic Dynamics in a Paradigmatic Model of Glass-Forming Molecular Liquid

Abstract: Glass transition is a most intriguing and long-standing open issue in the field of molecular liquids. From a macroscopic perspective, glass-forming systems display a dramatic slowing-down of the dynamics, with the inverse diffusion coefficient and the structural relaxation times increasing by orders of magnitude upon even modest supercooling. At the microscopic level, single-molecule motion becomes strongly intermittent, and can be conveniently described in terms of “cage-jump” events. In this work, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…The emergence of negative correlations among waiting times shows that the hopping between the two phases happens through some rearranging jumps, associated to the short waiting times detected right after a long one. In relation to this, a study appeared very recently [67] in which an analysis of the same system reported in this work is performed, highlighting deviations from CTRW and other theoretical macroscopic predictions at low temperatures. Interestingly, the presence of temporal correlations are listed as a possible reason behind such deviations, thus emphasising the relevance of the results reported here.…”
Section: Discussionsupporting
confidence: 59%
“…The emergence of negative correlations among waiting times shows that the hopping between the two phases happens through some rearranging jumps, associated to the short waiting times detected right after a long one. In relation to this, a study appeared very recently [67] in which an analysis of the same system reported in this work is performed, highlighting deviations from CTRW and other theoretical macroscopic predictions at low temperatures. Interestingly, the presence of temporal correlations are listed as a possible reason behind such deviations, thus emphasising the relevance of the results reported here.…”
Section: Discussionsupporting
confidence: 59%
“…It was found that it can help explain the mechanisms responsible for such changes in gels and emulsions, which are usually heterogeneous [ 40 , 41 ]. Microrheological measurements (based on thermal movement of particles) and macroscopic measurements of mechanical properties (requiring external force, e.g., mechanical shear) complement each other in determining the detailed characteristics of gel systems [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…At variance with the two-dimensional system (Figure 4b), three-dimensional simulations in Figure 4a, at T = 0.45, are too short-lasting to verify whether any deviation from the λ(t) ∝ t 0.33 behaviour emerges or not at long time periods.For this reason, in Figure 5, we examine λ(t), as computed in [29], for the three-dimensional system at a slightly higher temperature, T = 0.5. It is interesting to note, in fact, that comparing the 3KALJ dynamics at T = 0.5 with the 2KALJ at T = 0.45 is particularly appropriate, since these two systems are at a similar "distance" from their respective Mode Coupling temperatures [43,45,46] and, therefore, similar dynamical features are expected. Now, at T = 0.5, the simulated dynamics is long enough (in terms of t/τ F ) to observe the same 0.33-to-0.5 power-law crossover in λ(t), as found in two-dimensions (Figure 4b), with the t 0.5 scaling stepping in charge at a similar time t/τ F 10.…”
Section: Displacement Distribution and Its Evolution In Two-and Three...mentioning
confidence: 99%